Enacting Citizenship Kurdish Women's Resilience, Activism and Creativity - Hamelink, Wendelmoet; Bocheńska, Joanna; Wiktor-Mach, Dobrosława; Kaczorowski, Karol; Hanoğlu, Hayal; Skupiński, Marcin; Hajiagha, Azad; Rodi Keskin, Hüseyin; Weiss, Nerina; Şen, Besime (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XXIV, 379 p. 12 illus., 10 illus. in color.